Simplified method for analysis of circular steel tubed-reinforced-concrete columns under eccentric compression. (1st November 2019) - Du, Panwei; Gan, Dan; Yang, Yaowen; Tan, Kang Hai
Highlights: A simple and general approach to analyse circular steel TRC columns is proposed. Directly determine column capacity by considering slenderness and eccentricity. Simple geometrical proof of classical Rankine formula is provided. Method to determined mid-height deflection at peak load is proposed. Model verification with test data shows a mean value of 0.977 and a COV of 0.076. Abstract: This paper develops a simple and general approach to analyse circular steel tubed- reinforced-concrete (TRC) columns including calculations of peak loads and plots of ascending branch of load-deflection curves. The proposed model relates cross-sectional capacity to actual column capacity by introducing a stability parameter so that column N-M curves can be determined directly. This stability parameter is calculated by establishing a rational mid-height deflection limit, which can be obtained through strain-compatibility and geometric relationship. It also provides a theoretical background to the classical Rankine formula. Moreover, a smooth transition of load-carrying capacity from short to slender columns is obtained. To generate the load-deflection curves, mid-height deflection is increased from 0 to the deflection limit while cross-sectional capacity is kept the same. The proposed method is validated against three series of test data including a total number of 40 TRC columns. It shows that the predictions compare well with the test results in three aspects, namely, mid-height deflection at peak load, peak load and ascending branch of the load-deflection curve. Moreover, the proposed method has a wide range of applications for TRC columns filled with both normal and high strength concretes with column slenderness ratio ranging from low to high. Most importantly, this model can be implemented using spreadsheet, which provides a simple and robust numerical tool for engineers to determine strength of TRC columns.